Droplet and Spray Transport: Paradigms and Applications - Basu, Saptarshi; Agarwal, Avinash Kumar; Mukhopadhyay, Achintya; Patel, Chetan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book focuses on droplets and sprays and their applications. It discusses how droplet level transport is central to a multitude of applications and how droplet level manipulation and control can enhance the efficiency and design of multiphase systems. Droplets and sprays are ubiquitous in a variety of multiphase and multiscale applications in surface patterning, oil recovery, combustion, atomization, spray drying, thermal barrier coating, renewable energy, and electronic cooling, to name but a few. This book provides two levels of details pertaining to such applications. Each chapter delves into a specific application and provides not only an overview but also detailed physical insights into the application mechanism from the point of view of droplets and sprays. All chapters provide a mix of cutting-edge applications, new diagnostic techniques and modern computational methodologies, as well as the fundamental physical mechanism involved in each application. Taken together, the chapters provide a translational perspective on these applications, from basic transport processes to optimization, and from design to implementation using droplets or sprays as fundamental building blocks. Given its breadth of coverage, the book will be of interest to students, researchers, and industry professionals alike.
Part I: General -- Introduction to Application Paradigms of Droplets and Spray Transport -- Part II: Transport Phenomena in Droplets and Sprays of Non-Newtonian and Complex Fluids -- Drop Impact Dynamics of Newtonian and Non-Newtonian Liquid. Spray in Polymer Processing -- Transport Phenomena in Functional Droplets -- Drop Breakup and Size Evolution in Oil and Gas Production: A Review of Models and Mechanisms -- Drops, jets and high-resolution 3D printing: Fundamentals and applications -- Part III Droplet and Spray Transport in Presence of Phase Change -- Coalescence Characteristics of Liquid Drops with Application to Dropwise Condensation -- Molten Drop to Coolant Heat Transfer during Premixing of Fuel Coolant -- Harvesting Water from Natural and Industrial Fogs - Opportunities and Challenges -- Thermal Management of Electronics using Sprays and Droplets -- Part IV Interaction of Droplets and Sprays with Surface -- Droplet Impact on Solid Surfaces -- Sprays used for Thermal Barrier Coatings -- PartV Droplet and Spray Transport at Microscale -- Droplets in Microfluidics.
Keywords: Fluid mechanics; Soft condensed matter; Chemistry, Technical; Engineering Fluid Dynamics; Soft and Granular Matter; Industrial Chemistry